Rapidly Growing Iris Melanocytoma with Secondary Glaucoma in a 6-Year-Old Child. Issue 4 (July 2016) - Sharma, Vishal; Finger, Paul T.; Sidoti, Paul A.; Semenova, Ekaterina; Iacob, Codrin E.
Purpose: To describe an unusual case of pediatric iris melanocytoma with pigment dispersion glaucoma that resolved after resection of the primary tumor. Methods: Retrospective case review of the clinical record, ultrasonographic images, and histopathology. Results: A 6-year-old Asian girl, with a dark iris tumor, pigment dispersion, and secondary glaucoma, was initially treated with topical antiglaucoma medication and observation. Rapid growth prompted biopsy, revealing melanocytoma. As the tumor continued to grow, excision of the primary tumor was performed. Surgery proved curative in that the pigment dispersion slowly reabsorbed and her glaucoma resolved. Conclusions: In this case, rapid growth did not indicate malignant transformation. Initial observation for growth and judiciously timed surgical intervention prevented progression, loss of vision, and potentially the loss of the eye.